1995
DOI: 10.1002/prac.19953370176
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis ofN-acetylmuramic acid derivatives as potential inhibitors of the D-glutamic acid-adding enzyme

Abstract: Compounds containing N-acetyl-D-muramic acid and (L-1-aminoethy1)phosphonic acid were designed as potential inhibitors of the D-glutamic acid-adding enzyme of the biosynthesis of bacterial peptidoglycan.)phosphonic acid dimethyl ester]-c~,P-D-glucopyranose (9) was also prepared and was submitted to the MacDonald reaction in order to introduce a phosphate group on the anomeric position. A complex mixture of phosphorylated orland methylated derivatives of 3 was obtained. They were purified by h.p.1.c. and charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The overall yield of this approach was very low (13%), which was mostly due to the poor conversion of 17 to 18 in the first reaction step. The title 2,4-disubstituted aniline 12i was therefore synthesised using a different approach, starting from commercially available methyl 2-amino-5-furoate (20) and methyl acrylate, following a literature procedure [40]. After DielseAlder reaction in the first step the aminosubstituted 7-oxabicyclo[2.2.1]heptene 21 was spontaneously converted to substituted aniline 22.…”
Section: Chemistrymentioning
confidence: 99%
“…The overall yield of this approach was very low (13%), which was mostly due to the poor conversion of 17 to 18 in the first reaction step. The title 2,4-disubstituted aniline 12i was therefore synthesised using a different approach, starting from commercially available methyl 2-amino-5-furoate (20) and methyl acrylate, following a literature procedure [40]. After DielseAlder reaction in the first step the aminosubstituted 7-oxabicyclo[2.2.1]heptene 21 was spontaneously converted to substituted aniline 22.…”
Section: Chemistrymentioning
confidence: 99%
“…As for substrate analogues, the effect of various analogues of d ‐glutamic acid on the E. coli enzyme was investigated, and a few displayed weak inhibition (Pratviel‐Sosa et al ., 1994). In addition, N ‐acetylmuramic acid derivatives were also synthesized and tested as potential inhibitors of MurD, but no promising inhibitors resulted from that approach (Auger et al ., 1995).…”
Section: Structure and Catalysis Of Amino Acid Ligasesmentioning
confidence: 99%
“…Its high (stereo)specificity for D-glutamic acid has been shown by studying structurally related analogues tested as substrates or inhibitors. 21,22 There have been several successful attempts to identify MurD inhibitors by using the transition-state hypothesis [23][24][25][26][27][28][29] and it was suggested that D-glutamic acid represents an essential fragment of a potent inhibitor. 25,26 Based on this rationale we recently synthesized a series of sulfonamide derivatives of D-glutamic acid, as analogues of the tetrahedral intermediate (unpublished results).…”
Section: Introductionmentioning
confidence: 99%